Racial and Insurance-related Disparities in Delivery of Immunotherapy-type Compounds in the United States. Issue 2 (February 2019) - Verma, Vivek; Haque, Waqar; Cushman, Taylor R.; Lin, Chi; Simone, Charles B.; Chang, Joe Y.; McClelland, Shearwood; Welsh, James W.
Abstract : Racial and/or socioeconomic factors affect the type of therapies delivered for non–small cell lung cancer (NSCLC). Given the rapid expansion of immunotherapy for NSCLC, it is a crucial public health priority to evaluate disparities in administration thereof. The National Cancer Database (NCDB) was queried for newly diagnosed metastatic NSCLC. Patients were dichotomized based on receipt of immunotherapy-type compounds (ICs) based on NCDB coding. Multivariable logistic regression ascertained factors associated with IC delivery. Subgroup analysis, performed by univariate logistic regression modeling, evaluated the effect of race while stratifying for insurance type. Of 504, 447 patients, 11, 420 (2.3%) received ICs, and 493, 027 (97.7%) did not. From 2004 to 2012, ⩽1% of patients received ICs; however, 4.9% did so in 2013, 6.6% in 2014, and 8.7% in 2015. ICs were more likely administered to younger and healthier patients, those living farther from treating facilities, and in more educated areas ( P <0.05 for all). ICs were more often delivered to adenocarcinomas, and patients who received chemotherapy but not radiotherapy ( P <0.05 for all). In addition to geographic differences, uninsured and Medicaid populations received ICs less often, along with African Americans. On subgroup analysis, African Americans were less likely to receive ICs even when stratified for Medicare, Medicaid, or private insurances. Because IC utilization is expected to amplify even further going forward, these public health and economic issues are essential to identify and address appropriately, and have implications on pharmaceutical/insurance companies, value-based oncology, and public health policy. Methods to address these inequalities are also discussed.